Estudo e simula??o de sistemas CDMA multiportadora - Silva, F?bio Rodrigues da (2010)
This dissertation presents concepts and simulation results concerning some multicarrier code-division multiple access (MC-CDMA) systems. They use frequency spread coding (FSC) as a means for providing diversity without the explicit addition of any redundancy in time or frequency. They also use double spreading code (DC) per user as a mean for combating the multiuser interference (MUI) in the downlink of a cellular mobile communication system. After a theoretical review about some fundamental concepts, a reference CDMA system is presented and two modifications of this system are proposed and analyzed. These modifications are related to the incorporation of the FSC and DC techniques. Simulation results are then presented and discussed.